The Mediation Effect of Work Discipline in the Relationship Between School Culture and Academic Supervision and Teacher Performance in Public Senior High Schools in Magelang City - Prasetyo, Taat; Fakhruddin, Fakhruddin; Cahyaningdyah, Dwi (Educational Management, 2022)
The aim of this research is to better understand how work discipline mediates the relationship between school culture, academic supervision, and teacher effectiveness. The success of a leader can be judged by how well they carry out their duties as a leader, which include putting plans into action, taking decisive action, and overseeing others. How well instructors accomplish their jobs is influenced by factors such as school culture, academic supervision, and workplace discipline. This study employed a quantitative approach to research. There were 162 educators from Magelang city's public high schools used as a sample for this research. The data was collected using a cluster proportional sampling method. The validity and reliability of the questionnaire employed in the study were established beforehand. Path analysis and partial least squares (PLS) were employed to examine the mediator variable in the data analysis for hypothesis testing. Results There was a correlation between teacher effectiveness and school climate, administrative support, and workplace rules and regulations. The relationship between work culture and academic management was mediated by workplace discipline. It follows that a teacher's effectiveness in the classroom can be improved by instituting stricter work rules and procedures.